Simple quantitation of formoterol and 11-nor-Delta(9)-tetrahydrocannabinol-9-carboxylic acid in human urine by liquid chromatography-tandem mass spectrometry in doping control - Lee, Kang Mi; Kim, Ho Jun; Son, Junghyun; Park, Ju-Hyung; Kwon, Oh-Seung; Lee, Jaeick (ELSEVIER SCIENCE BV, 2014)
11-nor-Delta(9)-tetrahydrocannabinol-9-carboxylic acid (THC-COOH) and formoterol are newly revised prohibited threshold substances (150 ng/mL for THC-COOH and 40 ng/mL for formoterol) by the World Anti-Doping Agency (WADA). In continuation of our direct quantitation work of the prohibited threshold substances, direct LC-MS/MS methods combined with a simple sample preparation procedure have been developed and validated for the measurement of these two threshold substances in urine samples. After the enzymatic hydrolysis of urine samples, the resulting samples were diluted with acetonitrile and centrifuged. The supernatant was directly analyzed by LC-MS/MS using the selected reaction monitoring mode. The calibration curve range of the assay was ranged over 50-200% of the threshold value according to WADA guidelines. The limit of detection and limit of quantification were 6.1 and 18.4 ng/mL for THC-COOH and 2.0 and 6.2 ng/mL for formoterol, respectively. Intra- and inter-day precisions were between 2.08% and 7.28% and the accuracies ranged from 95.16% to 104.49%. The present methods were successfully applied to the analysis of the proficiency test samples. (C) 2014 Elsevier BM. All rights reserved.